A Just Standard: The Ethical Management of Incidental Findings in Brain Imaging Research. Issue 2 (2021) - Graham, Mackenzie; Hallowell, Nina; Savulescu, Julian
Abstract: Neuroimaging research regularly yields "incidental findings": observations of potential clinical significance in healthy volunteers or patients, but which are unrelated to the purpose or variables of the study.